2019
DOI: 10.3390/en12091775
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers to Industrial Energy Efficiency in Textile Industries of Bangladesh

Abstract: Bangladesh faced a substantial growth in primary energy demand in the last few years. According to several studies, energy generation is not the only means to address energy demand; efficient energy management practices are also very critical. A pertinent contribution in the energy management at the industrial sector ensures the proper utilization of energy. Energy management and its efficiency in the textile industries of Bangladesh are studied in this paper. The outcomes demonstrate several barriers to energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 48 publications
3
33
2
2
Order By: Relevance
“…Concerning the adoption of these strategies, during the manufacturing processes, energy usage should be monitored and this is affected by product type, machines used and state of the final product [112]. Technologies like photovoltaic panels to produce energy, sensorized glasses to adjust heat and light inside the building and water reuse technologies are used for the right implementation of these strategies [113].…”
Section: Closed-loop Supply Chain and Reverse Logisticsmentioning
confidence: 99%
“…Concerning the adoption of these strategies, during the manufacturing processes, energy usage should be monitored and this is affected by product type, machines used and state of the final product [112]. Technologies like photovoltaic panels to produce energy, sensorized glasses to adjust heat and light inside the building and water reuse technologies are used for the right implementation of these strategies [113].…”
Section: Closed-loop Supply Chain and Reverse Logisticsmentioning
confidence: 99%
“…In academic literature, energy management is portrayed as a holistic combination of applying resources, conversion, and application of energy [16,20,25,32]. The system involves checking, auditing, recording, scrutinizing, and more importantly controlling the energy flows to ensure the minimum consumptions of energy but to achieve maximum energy productivity [16,42]. Academicians have pointed some of the minimal prerequisites for implementation and operation of energy management in the industries [27,40,41,43,44].…”
Section: Of 21mentioning
confidence: 99%
“…However, industrial energy efficiency still remains unattained [9,10]; with low implementation rates of energy efficiency measures [11,12] because of certain barriers [13,14], although research has shown its immense potential. There are multiple studies conducted at local, regional, national, and multinational focusing the barriers to adopt energy efficiency in the industries [15][16][17][18][19]. On the contrary, the drivers are also found towards energy-efficient technology adoption by several studies [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…• strictly market-related factors, such as awareness of actual energy costs, anticipating high market prices of energy in the future and subsequent attempts to constrain energy-related company costs, or availability of favorable loans for EE financing [20]; • advances within the organization and management, including the adoption of environmental management systems [21], benchmarking against competitors within a given industry, or enhancing supply chain management within a company [22]; • technological progress [23]; • environmental regulation at both national and regional levels [24], including increasing energy tariffs [25], drawing voluntary programs and agreements between industry and governing bodies that feature negotiated targets and timetables, as well as threatening to introduce future taxes/regulation [26].…”
Section: Of 16mentioning
confidence: 99%